Withdrawal-Associated Increases and Decreases in Functional Neural Connectivity Associated with Altered Emotional Regulation in Alcoholism - O'Daly, Owen G; Trick, Leanne; Scaife, Jess; Marshall, Jane; Ball, David; Phillips, Mary L; Williams, Stephen SC; Stephens, David N; Duka, Theodora (Neuropsychopharmacology (New York, N.Y.), 2012)
Alcoholic patients who have undergone multiple detoxifications/relapses show altered processing of emotional signals. We performed functional magnetic resonance imaging during performance of implicit and explicit versions of a task in which subjects were presented with morphs of fearful facial emotional expressions. Participants were abstaining, multiply detoxified (MDTx; n=12) or singly detoxified patients (SDTx; n=17), and social drinker controls (n=31). Alcoholic patients were less able than controls to recognize fearful expressions, and showed lower activation in prefrontal areas, including orbitofrontal cortex and insula, which mediate emotional processing. The decrease in activation was greater in MDTx patients who also showed decreased connectivity between insula and prefrontal areas, and between amygdala and globus pallidus. In the explicit condition, the strength of connectivity between insula and areas involved in regulation of emotion (inferior frontal cortex and frontal pole) was negatively correlated with both the number of detoxifications and dependency (measured by the severity of alcohol dependency (SADQ) and control over drinking score (Impaired Control questionnaire, ICQ)). In contrast, increased connectivity was found between insula and the colliculus neuronal cluster, and between amygdala and stria terminalis bed nucleus. In the implicit condition, number of detoxifications and ICQ score correlated positively with connectivity between amygdala and prefrontal cortical areas involved in attentional and executive processes. Repeated episodes of detoxification from alcohol are associated with altered function both in fear perception pathways and in cortical modulation of emotions. Such changes may confer increased sensitivity to emotional stress and impaired social competence, contributing to relapse.